Granville S. Allison diary - Allison, Granville S., 1867-1908.
Diary (1887 June 21-August 6) kept by Allison while traveling in England beginning with an entry for Queen Victoria's Jubilee Day, June 21, in which he describes the royal family and the parade to Westminster Abbey. Allison mentions visits to tourist sites including various museums, Roman ruins, Canterbury Cathedral, Hyde Park, and London Bridge. He also describes his attendence at the theater and opera, a tour of the Times, a trip to Bayswater to see the fire that burned London department store Whiteleys as well as day trips via bicycle, boat, and train.
Episcopal priest.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Victoria, -- Queen of Great Britain, -- 1819-1901 -- Anniversaries, etc; Victoria, -- Queen of Great Britain, -- 1819-1901 -- Family; Canterbury Cathedral; Westminster Abbey; Whiteleys (Department store); Times (London, England); Museums -- England; Opera -- England; Parades -- England; Ruins -- England; Theater -- England; England -- Description and travel; Great Britain -- Social life and customs -- 19th century; Hyde Park (London, England); London Bridge (London, England); Clergy